Analýza pacientov s akútnou hepatitídou E na Klinike infektológie a cestovnej medicíny v Košiciach - Sekula, J; Paraličová, Z (Epidemiologie, mikrobiologie, imunologie, 2024)
AIM: To analyse clinical, laboratory, and epidemiological data of a cohort of patients with acute hepatitis E treated at the Clinic of Infectology and Travel Medicine (CITM) in Košice. MATERIAL AND METHODS: Retrospective analysis of hospital information system data on patients diagnosed with acute hepatitis E who were examined or hospitalized at CITM in 2015-2023. Statistical evaluation of the available data with a focus on epidemiology, course, and complications. RESULTS: The cohort consisted of 62 patients. Fifty-eight percent were male. The mean age was 56 years. Seventy-four percent of patients were hospitalized, with a mean length of hospital stay of 10 days. The most common clinical manifestation was jaundice (in 40% of patients). Six patients had stool HEV RNA testing and all were confirmed to have genotype 3. In 5% of patients, the infection was classified as imported (they did not have HEV RNA tested), and 95% of cases were autochthonous. A history of contact with an HEV infected person was reported by 26% of patients. A history of preexisting liver disease was noted in 13% of patients who were confirmed with higher bilirubin, GMT, and ammonia levels. No statistically significant differences were found for patients with a history of immune deficiency. One patient with preexisting liver disease developed fulminant infection resulting in death. Four hepatitis E patients with neurological symptoms had lower bilirubin levels. CONCLUSIONS: The study cohort included predominantly older men. Genotype 3 was confirmed in all patients who underwent HEV RNA testing. Higher bilirubin, ammonia, and GMT levels were confirmed in patients with preexisting liver disease. Patients with neurological complications had lower bilirubin levels. One patient with preexisting liver disease died.
Keywords: Travel Medicine; dospělí; Female; Acute Disease; virus hepatitidy E; Hepatitis E virus; Adult; mladý dospělý; ženské pohlaví; lidé; Hepatitis E; Italy; autochthonous hepatitis E; Itálie; Aged, 80 and over; cestovní lékařství; retrospektivní studie; Male; acute hepatitis E; Aged; Young Adult; hepatitis E; akutní nemoc; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Retrospective Studies; Middle Aged; hepatitida E; Humans